AAAAI-EAACI PRACTALL: Standardizing oral food challenges-2024 Update - Sampson,HA; Arasi,S; Bahnson,HT; Ballmer-Weber,B; Beyer,K; Bindslev-Jensen,C; Bird,JA; Blumchen,K; Davis,C; Ebisawa,M; Nowak-Wegrzyn,A; Patel,N; et al. (Pediatric Allergy and Immunology, 2024)
This common statement of the American Academy of Allergy, Asthma and Immunology (AAAAI) and The European Academy of Allergy and Clinical Immunology (EAACI) provides an update of the 2012 published guidelines on food challenges. The guidelines equally address food challenges in the research and the clinical settings. They first address the diagnostic tests which can guide the decision to conduct a challenge. Safety of food challenges is prime, and the various procedures and safety issues as well as medications potentially involved in challenges are extensively discussed. Challenges are suggested to be conducted with semi-logarithmic incremental doses based on the protein content, typically for IgE-mediated food allergy with intervals of 20–30 min between doses. Specific protocols for other types of reactions such atopic dermatitis or gastrointestinal food allergy are detailed separately. Proper stopping criteria are essential in order to reduce the risk of false-positive diagnoses, but also severe reactions. The guidelines recommend criteria based on “go on,” “stop,” or “observation.” These revised guidelines will clearly provide much needed guidance for food challenges in the research and clinical settings. They will continue to evolve with new diagnostic tests or new needs in the field of food allergy.